Gas chromatography mass spectometry analysis of Volatile compounds in ethanolic extract of propolis from geniotrigona thoracica of malaysian Stingless bees species - MUHAMMAD SYAMIL MOHD SUIB; ESHAIFOL AZAM OMAR; WAN ADNAN WAN OMAR; RAFEEZUL MOHAMED (International Journal of Pharma and Bio Sciences, 2018)
Geniotrigona Thoracica (G. Thoracica) is one of the stingless bees species found in Malaysia. It produces propolis, a sticky resinous material comprises of exudates and bud of plants collected at the bee hive neighboring that are blend together with wax and bee enzyme. Its chemical composition varies which exerts various pharmacological activities.The aim of this study to investigate the volatile compounds in ethanolic extract of propolis (EEP) from G. Thoracica. Propolis from three different colonies of G. Thoracica. Were collected and extracted using 80% ethanol. The volatile compounds present in the EEP of three colonies were analysed using Gas Chromatography Mass Spectometry (GC-MS). The peaks in the chromatogram were integrated and compared with the database of spectrum of known compounds in the National Institute of Standards and Technology (NIST) library. EEP of G. Thoracica from all colonies of stingless bees composed of eight volatile compounds namely Oleyl alcohol, 4,4,6a,6b,8a,11,11,14 Octamethyl 1,4,4a,5,6,6a,6b,7,8,8a,9,10,11,12,12a,14,14a,14b-octadecahydro-2H-picen-3-one, alpha.-Amyrin, Cycloartenol, 2-Methoxy-4-vinylphenol, (9Z)-octadeca-9,17-dienal, beta.-Amyrin and Urs-12-en-24-oic acid. There were four triterpenoids derivatives, one phenolic acid derivatives, one unsaturated fatty alcohol derivatives and one unsaturated aldehyde derivatives were also detected in the EEP of G. Thoracica. These volatile compounds and its derivatives have been found to pose various anti-inflammatory responses that may help in curing various diseases.